Digital Marketing of Brand Awareness (At Daikin Kota Semarang) - Bagus Yunianto Wibowo; Misbakhul Arrezqi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to analyze the influence of Digital Marketing (X) on Brand Awareness (Y) on consumers of Daikin in Semarang City. The data collection method used in this research were questionnaires and literature study. The questionnaires used a Semantic. Differencial scale with a 10-point scale and the sample collecting method used was convenience random sampling on 100 consumers product in Semarang City. The data analysis method used were test of validity, reliability test, the coefficient determination, and t test. The results of the Digital Marketing variable (X) have a significant effect on Brand Awareness (Y).